The hammer and the flute : women, power, and spirit possession - Keller, Mary, 1964- (Johns Hopkins University Press, 2002)
"The possession of the body - particularly the body of a woman - by spirits, deities, and ancestors is a phenomenon common to a number of religions. Ethnographers have often studied cases of spirit possession to decode a society's cultural values and belief systems. In The Hammer and the Flute: Women, Power, and Spirit Possession, however, Mary Keller approaches the spirit possession of women as a historian of religion informed by postcolonial theory and feminist philosophy, challenging the prevalent interpretation that possessed women are victims of psychological disturbance or are actively manipulating their audiences. Proposing a new theoretical framework, "instrumental agency," Keller offers a far more nuanced portrait of spirit possession as a negotiation with multiple kinds of power which requires a radical receptivity on the part of the possessed persons and as a reorientation of scholarship."--Jacket